Analisis Pengaruh Etika Penjual terhadap Loyalitas Pelanggan pada Industri Otomotif - Resi Ario Bismo; Afif Zaerofi; Indra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of seller ethics on customer satisfaction, trust, and loyalty. Additionally, it aims to explore the impact of satisfaction and trust on customer loyalty within the automotive industry. Using a quantitative approach and survey method, data was collected from 95 automotive industry employees in the Jabodetabek-Karawang area via cluster sampling. A questionnaire was utilized for data collection, and the analysis was conducted using PLS SEM. The results indicate that seller ethics positively and significantly impact customer trust, satisfaction, and loyalty. Specifically, enhanced seller ethics correlate with higher customer satisfaction, strengthened customer trust, and increased customer loyalty. Moreover, high customer trust boosts loyalty, and customer satisfaction is crucial for fostering loyalty. These findings underscore the importance of seller ethics in cultivating robust and profitable customer relationships. By practicing good ethics in customer interactions, sellers can enhance trust, satisfaction, and loyalty. This study contributes to the automotive industry literature and has practical implications for companies, suggesting that improving salesperson ethical behavior through training and coaching can be beneficial.